2018
DOI: 10.12806/v17/i4/r10
|View full text |Cite
|
Sign up to set email alerts
|

Examining the (Lack of) Effects Associated with Leadership Training Participation in Higher Education

Abstract: This study examined the differences between a multi-campus sample of university students who reported consistent participation in formal leadership development programs (n=414) and a comparison sample (n=153) with no prior experience across three diverse postsecondary institutions in the United States. Both samples were matched with regard to gender and racial identity, prior self-reported high school leadership training experience, and selfreported possession of formal leadership positions in co-curricular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The results provide some support for the potential for leadership programs to increase college students' confidence in their leadership capacity; however, the results also suggest that not all leadership programs provide ubiquitous effects on students' leadership efficacy. Thus, while providing partial support for research in which leadership programs have yielded benefits on students' leadership efficacy (Dugan et al, 2008;Kodama & Dugan, 2013), this study also provides support for other scholarship in which researchers have found no effects of leadership programming on students' leadership efficacy (Rosch, 2018). be feasible for many students because the associated time and financial commitment may conflict with other priorities, such as employment, academic work, and family responsibilities.…”
Section: Resultsmentioning
confidence: 55%
“…The results provide some support for the potential for leadership programs to increase college students' confidence in their leadership capacity; however, the results also suggest that not all leadership programs provide ubiquitous effects on students' leadership efficacy. Thus, while providing partial support for research in which leadership programs have yielded benefits on students' leadership efficacy (Dugan et al, 2008;Kodama & Dugan, 2013), this study also provides support for other scholarship in which researchers have found no effects of leadership programming on students' leadership efficacy (Rosch, 2018). be feasible for many students because the associated time and financial commitment may conflict with other priorities, such as employment, academic work, and family responsibilities.…”
Section: Resultsmentioning
confidence: 55%
“…As Bandura (1997) found, self-efficacy interacts with a person's knowledge and skills to lead some people to believe they can perform successfully while others believe they will fail. In Rosch's (2018) critique of existing leadership training programs, he posed the use of the "Ready, Willing, and Able" model of leadership education authored by Keating, Rosch, and Burgoon (2014) which argues that students should be supported in developing the self-efficacy (i.e., "Ready"), motivation ("Willing"), and skills to lead ("Able").…”
Section: Academic Peer Mentors College Students Canmentioning
confidence: 99%
“…Indeed, the field might be largely ignoring the fourth stage of Kolb' s (1984) model of experiential learning-the "active-experimentation" stage that ushers in real-time feedback on behavior effectiveness. Indeed, researchers have suggested that leadership courses already offer opportunities for learners to: (a) contemplate a concrete experience as a leader or follower, (b) critically reflect on that experience, and (c) engage in meaning-making from the critical reflection of said experience (Guthrie & Jenkins, 2018), but without providing opportunities for applying new skills and receiving formal feedback on their effectiveness, students' reported growth through participating in formal courses may largely disappear less than a year later (Rosch, 2018).…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…To be sure, research conducted with these designs provides value; however, their predominance is itself limiting. Emerging research seems to indicate that repeated measures design that collect data only when students are actively enrolled in the course (i.e., with no longitudinal follow‐up) may inflate the degree to which statistically significant findings indicate sustainable growth (Rosch, 2018). Similarly, while comparison studies almost universally show differences between groups, their research design inherently limits their ability to indicate the degree to which the educational experience itself contributes to such differences.…”
Section: Critiquing “What We Know”mentioning
confidence: 99%